2001
DOI: 10.1093/humrep/16.5.961
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden and acquired activated protein C resistance among 1000 women with recurrent miscarriage

Abstract: Activated protein C (APC) resistance, both in its congenital form, due to the factor V Leiden mutation, and in its acquired form, are important risk factors for systemic venous thrombosis. In view of the suspected thrombotic aetiology of some cases of recurrent miscarriage, the prevalence of APC resistance was determined among 1111 consecutive Caucasian women with a history of either recurrent early miscarriage (three or more consecutive pregnancy losses at <12 weeks gestation; n = 904) or a history of at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
3
9

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(117 citation statements)
references
References 33 publications
4
101
3
9
Order By: Relevance
“…Preston et al (1996), in a retrospective study, could not elicit a link between hereditary APCR and first and second-trimester losses either. In a larger study, Rai et al (2001), found a similar prevalence of factor V Leiden in patients with first and second trimester losses compared to a control group of parous women. A composite study of the association between the known thrombophilias and fetal loss demonstrated that fetal loss occurred among 10 of 48 women with thrombophilia (21%), and among 10 of 60 control women (17%).…”
Section: Hereditary Apcr (Factor V Leiden) and Pregnancy Lossmentioning
confidence: 78%
See 1 more Smart Citation
“…Preston et al (1996), in a retrospective study, could not elicit a link between hereditary APCR and first and second-trimester losses either. In a larger study, Rai et al (2001), found a similar prevalence of factor V Leiden in patients with first and second trimester losses compared to a control group of parous women. A composite study of the association between the known thrombophilias and fetal loss demonstrated that fetal loss occurred among 10 of 48 women with thrombophilia (21%), and among 10 of 60 control women (17%).…”
Section: Hereditary Apcr (Factor V Leiden) and Pregnancy Lossmentioning
confidence: 78%
“…However, this study deviated from the definition of recurrent miscarriage and included patients with just one first or a single second trimester loss, and consequently, there was only one patient who had recurrent miscarriage and acquired APCR. More recently, a larger case control study found acquired activated protein C resistance to be significantly higher in women with recurrent early miscarriage 8.8% (80/904) as well as late miscarriage 8.7% (18/207) compared with controls 3.3% (5/150) (Rai et al, 2001). Rai et al clearly distinguished between hereditary and acquired activated protein C resistance, and indeed emphasised the importance of the latter in pregnancy loss, but used a more general classification of pregnancy loss.…”
Section: Acquired Apcr and Pregnancy Lossmentioning
confidence: 98%
“…Not all studies have supported the finding of hypofibrinolysis and thrombophilia in women with recurrent miscarriages. In an observational study 22 , 1000 consecutive women with unexplained recurrent pregnancy loss were compared with a control group of women with no history of recurrent pregnancy loss. Results showed that acquired activated protein C (APC) resistance, but not congenital Factor V Leiden mutation, was associated with miscarriage.…”
Section: Gonadotropinsmentioning
confidence: 99%
“…Normal gebelikte fizyolojik olarak APCR'de artış olur. Ancak altta yatan faktör V Leiden mutasyonu veya APCR olan olgularda bu fizyolojik değişiklik daha abartılı hale gelip fetal kayıp için daha yüksek risk oluşturur 12 . Faktör V Leiden mutasyonu ve TGK arasında pozitif ilişkiyi gösteren bir çok çalışma vardır 13 .…”
Section: Koagülasyon Sistemi Bozukluklarıunclassified